Odkrivanje raka dojk - Takač, Iztok (Obzornik zdravstvene nege, 1998)
Breast cancer detection methods are presented. In the sense of detection of this most frequent gynaecologic cancer, history, clinical investigation, mammography, ultrasound, fine needle and excisional biopsy are used. In some women cancer occurs more frquently, but it's occurrence can not be predicted yet. History allows us to select women at higher risk of developing breast cancer and to find symptoms, related to this disease. Clinical investigation of the breasts is an obligate part when investigating a woman. Currently, mammography is the most accurate method in breast cancer detection. Ultrasound is an additional method, which allows correct diagnosis in some cases. Fine needle and excisional biopsy allow us to confirm the presence of malignant cells. Screening of asymptomatic women by clinical investigation and mammography is an effective method for the detection of early cancer forms. Together with adequate treatment it will decrease the mortallity due to this disease.
Keywords: breast; breast neoplasms; diagnosis; diagnostika; dojke; rak (medicina)